2017
DOI: 10.1371/journal.pone.0183207
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and severity of acute mountain sickness and associated symptoms in children trekking on Xue Mountain, Taiwan

Abstract: BackgroundAcute mountain sickness (AMS) occurs in non-acclimatized people after an acute ascent to an altitude of 2,500 m or higher. The aim of this study was to examine the incidence and severity of AMS and associated symptoms in children.MethodsThe prospective observational study included 197 healthy, non-acclimatized 11 and 12-year-old children trekking the round-trip from the trailhead to the summit of Xue Mountain, Taiwan (2,179 m to 3,886 m) over 3 days. AMS was evaluated at Qika Hut (2,460 m) on Day 1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…Previous literature showed conflicting and inconclusive associations between age and AMS (Wang et al, 2010 ; McDevitt et al, 2014 ; Tang et al, 2014 ; Chan et al, 2016 ; Gonggalanzi et al, 2016 ; Cheng et al, 2017 ; Wu et al, 2018 ). This is predominantly due to the heterogeneity in study location, design, population, AMS diagnostic tool, and, most importantly, the small number of older adults included in the studies (Wu et al, 2018 ; Gianfredi et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous literature showed conflicting and inconclusive associations between age and AMS (Wang et al, 2010 ; McDevitt et al, 2014 ; Tang et al, 2014 ; Chan et al, 2016 ; Gonggalanzi et al, 2016 ; Cheng et al, 2017 ; Wu et al, 2018 ). This is predominantly due to the heterogeneity in study location, design, population, AMS diagnostic tool, and, most importantly, the small number of older adults included in the studies (Wu et al, 2018 ; Gianfredi et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In 2017, Fei-Ying performed an intervention on 11 to 12 years old children at 3100 m, reporting an AMS incidence between 23.4% and 29.4%. Cheng et al reported a 40.6% of AMS incidence on 197 healthy, non-acclimatized 11 and 12 years old children trekking the round-trip from the trailhead to the summit of Xue Mountain, Taiwan (2179 m to 3886 m), over 3 days [ 19 ]. In a similar study, Chan et al reported a 59% incidence of AMS in a cohort of 96 healthy non-acclimatized children aged 11–12 years who trekked from an elevation of 2600 m to 3952 m in 3 days (Jade Mountain, Taiwan).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have found no differences between females and males [ 17 , 18 ]. While a study has shown that females present a higher prevalence of AMS [ 8 ], other studies indicate that males present higher AMS than females [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of AMS is relatively high, from 23.9% to 53%, [ 24 26 ] in people accessing high altitude in a short period of time. Also, high altitude encephaledema or pneumonedema, which is a potentially fatal condition, is seen in 0.1% to 10% of people with AMS.…”
Section: Discussionmentioning
confidence: 99%